ASEAN Economic Growth: The Influence of Inflation, Trade, and Industrial Policy - Basuki, Agus Tri (Lembaga Riset Ilmiah, 2025)
This study aims to analyze the factors that affect economic growth in ASEAN countries, namely Singapore, Indonesia, Malaysia, Thailand, and the Philippines, during the period 1986-2022 using data from the World Development Indicators (WDI). The regression method is used to identify the impact of variables such as inflation, exchange rate, industrial value added (IVA), labor, interest rates, tax revenues, trade value, population, and investment on economic growth. The results of the study show that industrial value added (IVA), tax revenue (Tax_rev), and trade value (TRADE) have a significant influence on the economic growth of ASEAN countries. On the other hand, inflation has a negative effect on economic growth in Singapore, Malaysia, and the Philippines. In addition, the workforce has a positive influence on economic growth in Indonesia, Singapore, and Malaysia. These findings provide important insights for policymakers in ASEAN to pay attention to structural factors such as industrial policies, taxation, and trade in supporting sustainable economic growth. The main contribution of this study is to provide an in-depth empirical analysis of the factors influencing the economic growth of ASEAN countries, as well as their implications for economic policies in the region.